Isolation, separation, identification, and quantification of bioactive methylated flavone regioisomers by UHPLC‐MS/MS. Issue 7 (5th May 2021) - Noreen, Hafiza; Smith, Edward N.; Farman, Muhammad; Claridge, Tim D.W.; McCullagh, James S.O.
Abstract: Methylated flavones, commonly found in many plants of the Brassicaceae family, have potent antioxidant and anticancer activity with diverse therapeutic potential. However, the specific regioisomers of methylated flavones can have significantly different biochemical and potentially therapeutic properties as shown by various bioassays but analytically differentiating these compounds has been technically challenging and rarely reported. In this study, we demonstrate differentiation and identification of selected bioactive methylated flavone regioisomers, namely 5, 7, 3′‐trihydroxy‐4′‐methoxyflavone, and 5, 7, 4′‐trihydroxy‐3′‐methoxyflavone extracted from Coronopus didymus, a member of the Brassicaceae family, using ultra‐performance liquid chromatography coupled with electrospray ionization quadrupole time‐of‐flight tandem mass spectrometry (UPLC‐ESI‐QTOF‐MS/MS). Characteristic MS/MS product ions produced from neutral loss of carbon monoxide, and a methyl radical from the [M‐H] – ion, exhibited differential relative abundances attributed to different structural stabilities under the same activation and collision‐induced dissociation conditions. MS/MS also provided structural information which was sufficient to differentiate the methylated regioisomers and determine the position of the methyl group based on interpretation of their respective fragmentation patterns. Quantification showed 5, 7, 4′‐trihydroxy‐3′‐methoxyflavone was at least 1.60 mg per 10 g plant material in C. didymus extracts. This study demonstrates a straightforward and novel approach to rapidly differentiate, identify and quantify regio‐isomeric methylated flavone natural products using reversed‐phase UPLC‐MS/MS.